An APL program for the distribution of energy deposition by charged particles passing through thin absorbers - Howell, Leonard W. (Journal of statistical computation and simulation, 1985)
In passing through matter charged particles lose energy by collision with atomic electrons.This loss is subject to variation which must be included in energy loss estimation. This paper presents A Programming Language (APL) computer program which numerically evaluates the probability density function (PDF) for the energy deposited in a thin absorber by a charged particle. Researchers involved in analytical models of energy loss due to the interaction of charged particles with matter or in Monte Carlo simulations of cosmic rays which consider energy transfers will find this program to be a very practical means of evaluating the stochastic behavior of energy loss in thin absorbers by charged particles. The program makes full use of APL's array handling features to eliminate the annoying looping procedures typically associated with numerical integration, and its graphical output is extremely useful for studying the sensitivity of model parameters.